Kontribusi Sektor Pertanian Terhadap Perekonomian Kabupaten Banjarnegara - Fortunika, Sevi Oktafiana; Istiyanti, Eni; Sriyadi, Sriyadi (Universitas Muhammadiyah Yogyakarta, 2017)
The economics development in Banjarnegara regency have not maximum undertaken, therefore, the sector analysis is needed to formulate appropriate strategies. This study aims to know contribution, linkage and diffusion of agriculture sector to the other sectors, multiplier effect, and the priority sector in the economy of Banjarnegara regency. This research used input-output table of domestic transaction based on producer prices of Banjarnegara regency in 2013. The results showed that the agriculture sector which was dominated by subsector of food crop has high contribution to the economy of Banjarnegara regency. The agriculture sector has the highest forward linkage value after the industrial sector, but the backward linkage value is very low. The agricultural sector has the high enough for diffusion sensitivity value but the diffusion coefficient is very low. The highest sensitivity and coefficient in agricultural sector are the food crop. Multiplier income and employment in agricultural sector have the highest value while multiplier output is the second rank after industrial sector. The priority sector is industrial sector, then followed by agricultural sector which has subsector priority in food crop.